2007
DOI: 10.1590/s1678-77572007000600011
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of clinical periodontal conditions in smokers and non-smokers

Abstract: Given that tobacco smoking habit is a risk factor for periodontal diseases, the aim of this study was to compare clinical periodontal aspects between smokers and non-smokers. The clinical status were assessed in 55 patients, 29 smokers and 26 non-smokers, aged 30 to 50 years, with mean age of 40. The clinical parameters used were: probing depth (PD), plaque index (PI), gingival index (GI), clinical attachment level (CAL), gingival recession (GR) and gingival bleeding index (GBI) for arches (upper and lower) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0
6

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 28 publications
4
18
0
6
Order By: Relevance
“…1 Smoking is the major risk factor in the prevalence, extent and severity of periodontal diseases. [2][3][4][5] Cross-sectional studies have shown that smokers are two to seven times more likely to present periodontitis, compared to nonsmokers, 2,6,7 and smoking has been associated with tooth loss during periodontal maintenance as well. 7,8 With respect to surgical or non-surgical periodontal therapy, several studies have shown that smokers have a worse response to treatment when compared to nonsmokers.…”
Section: Introductionmentioning
confidence: 99%
“…1 Smoking is the major risk factor in the prevalence, extent and severity of periodontal diseases. [2][3][4][5] Cross-sectional studies have shown that smokers are two to seven times more likely to present periodontitis, compared to nonsmokers, 2,6,7 and smoking has been associated with tooth loss during periodontal maintenance as well. 7,8 With respect to surgical or non-surgical periodontal therapy, several studies have shown that smokers have a worse response to treatment when compared to nonsmokers.…”
Section: Introductionmentioning
confidence: 99%
“…Maksiller implant failleri sigara içenlerde (%10.9) içmeyen veya sigarayı bırakmış bireylere(%6.4) göre daha fazla görülmektedir (67). Güncel bir TARTIŞMA Sigara içimi periodontal hastalığın görülme olasılığı ve hastalığın şiddeti için majör bir risk faktörüdür (80). Kesitsel çalışmalar sigara içenlerin periodontitise yatkınlığının, sigara içmeyen bireylere göre 2-7 kat arttığını göstermektedir (81).…”
Section: İmplant Başarısıunclassified
“…There is a negative, dose-dependent relationship between smoking and periodontal health (63,64). Smokers are also more refractory to periodontal treatment than non-smokers (64).…”
Section: Smoking and Periodontal Diseasesmentioning
confidence: 99%